Cardiac surgery in older patients: hospital outcomes during a 15-year period from a complete national series. (11th November 2021) - Jones, James Mark; Loubani, Mahmoud; Grant, Stuart W; Goodwin, Andrew T; Trivedi, Uday; Kendall, Simon; Jenkins, David P
Abstract: OBJECTIVES: The objective was to review national trends in activity and hospital outcomes in older patients having cardiac surgery over a 15-year time period. METHODS: Data were collected prospectively and uploaded to the National Institute for Cardiovascular Outcomes Research electronically. Data were validated, cleaned and processed using reproducible algorithms. Mortality was death in hospital after index operation. RESULTS: A total of 227 442 cardiac procedures were recorded in patients aged ≥70 years of which 46 354 were in those aged ≥80 years. Overall patients aged ≥70 years represented 43% of all adult cardiac surgery in the most recent study year. The annual proportion of surgery in patients ≥80 years increased from 4.1% to 10.8% between the first and last study years. There has been a significant linear increase in octogenarian valve [β 67.44, 95% confidence interval (CI) 55.04 to 79.83, P  < 0.001] and coronary artery bypass graft surgery (β 32.53, 95% CI 6.16 to 58.90, P  = 0.020) patients. In-hospital mortality reduced significantly for patients aged 70–79 years (β −0.17, 95% CI −0.20 to −0.13, P  < 0.001) and all patients aged ≥80 (β −0.37, 95% CI −0.45 to −0.30, P  < 0.001). The median length of hospital stay was 7 days for 70–79 and 9 days for ≥80 group, compared with 7 days for the whole cohort <70 years. CONCLUSIONS: This study represents the largest complete validated national dataset of cardiac surgery in the entire population of older patients. Octogenarians represent 11% of adult patients having cardiac surgery by the end of the study period, a three-fold increase from the start. In-hospital mortality in patients aged ≥80 years halved during study period to only 4% despite high logistic EuroSCORE of 15%. Cardiac surgery in octogenarians places a higher demand on resources, however, with an increased postoperative length of stay. Abstract : The Society for Cardiothoracic Surgery (SCTS) in Great Britain and Ireland first established a cardiac surgery database in 1977 [1].